Analisis Perbandingan Kinerja Perusahaan Sebelum dan Sesudah Employee Stock Option Program (ESOP) (Studi Empiris pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia Tahun 2017-2020) - Rahmah, Siti; Asmeri, Rina; Bustari, Andre (Ekasakti Pareso Jurnal Akuntansi, 2024)
Implementation of the Employee Stock Option Program in this study aims to compare the company's performance both before and after the implementation of the Employee Stock Option Program for manufacturing companies listed on the IDX in 2017-2020. This research is a manufacturing issuer with as many as 193 companies. Purposive Sampling used in the sampling technique, so that a sample of 11 companies. Available analytical methods include descriptive statistical data analysis, normality test which also uses other tests (paired sample t test), and hypothesis testing with the Paired Sample Test and Wilcoxon test. The results of the study concluded that there were no differences in ROA, ROE, NPM, and TATO before and after the implementation of ESOP in manufacturing companies listed on the IDX for the 2017-2020 period.